AB0580 Clinical and Epidemiological Features and Management of BehÇEt Disease in A Brazilian Tertiary Hospital. (10th June 2014) - Lima Gomes Ochtrop, M.; Genovez, L.; Reis, T.; Oliveira, C.; Amorim, R.; Haddad, P.; Santos Bacchiega, A.B.
Abstract : Background: Behçet disease (BD) is prevalent in Central and East Asia and in the Eastern Mediterranean area where most studies have been performed. Although BD is one of the most common vasculitis in clinical practice only five studies have evaluated patients with BD in Brazil. Objectives: The objective of the study was to describe clinical manifestations of BD and their therapy in a single university hospital in Brazil. Methods: Tirty-six patients who met the International Study Group Criteria for BD and were under follow-up at the Vasculitis Unit of the Universidade do Estado do Rio de Janeiro were evaluated in a retrospective observational study. Results: Mean age at diagnosis was 28 (SD, 2, 82) years, and the female: male ratio was 1:1.4; 2 patients were brothers. The frequency of disease manifestations was as follows: oral ulcers, 100%; genital ulcers, 75%; pseudofolliculitis 47, 2%, erythema nodosum 30, 5%, articular involvement 58, 3%, gastrointestinal involvement, 2, 7%; ocular manifestations 30, 5%; retinal vasculitis 16, 6%. Neurologic involvement was seen in 27, 7% of patients: parenchymal lesions, 90%; aseptic meningitis, 40%; optic neuritis, 10%. Vascular manifestations were: venous thrombosis, 19, 4%; pulmonary embolism, 2, 7%; arterial aneurysm, 11% (coronary aneurysms 2, 7%; pulmonary artery aneurysms 8, 3%). Comorbidities were: systemic arterial hypertension, 33, 3%; diabetes mellitus, 11, 1%, dyslipidemia, 50%. The frequency of each treatment modality was as follows: colchicine, 83.3%; azathioprine, 69, 4%; methotrexate, 30, 5%; methylprednisolone pulses 25%; cyclophosphamide, 22, 2%; cyclosporine A, 2, 7%; and infliximab, 11, 1% (in patients with severe ocular involvement). Conclusions: The frequency of main clinical manifestations in this brazilian cohort follows those described in other endemic regions with higher frequency of neurologic, vascular and ocular involvement in men. Contrary to previously described in Brazil, higher disease prevalence was observed in men. This is the third study describing therapeutic modalities in a Brazilian cohort with predominating the use of azathioprine as immunosuppressive drug. References: Oliveira ACD et al. Behçt Disease - Clinical Features and Management in a Brazilian Tertiary Hospital. J Clin Rheumatol 2011;17: 416-420. Roberto Santos Tunes e col. Clinical aspects of behçet's syndrome in brazil: a review of 16 cases. Acta reumatol port. 2009;34:235-240. Fabricio Souza Neves e col. Faraway from the Silk Route: demographic and clinical features of Behçet's disease in 106 Brazilian patients. Clin Rheumatol (2009) 28:543–546. Sachetto Z et al. Behçet's disease in Brazilian patients: demographic and clinical features. Rheumatol Int (2012) 32:2063–2067. Aguiar SB, Guimarães S, Mesquita M, et al. Doença de Behçet: Estudo de 22 casos. Rev Bras Reumatol. 1997;37:66-74 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2588